A Modular Synthesis of Substituted Cycloparaphenylenes. Issue 8 (27th January 2022) - Kohrs, Daniel; Becker, Jonathan; Wegner, Hermann A.
Abstract: Herein, we report a modular synthesis providing access to substituted cycloparaphenylenes (CPPs) of different sizes. A key synthon introducing two geminal ester units was efficiently prepared by [2+2+2] cycloaddition. This building block can be conveniently converted to macrocyclic precursors controlling the ring size of the final CPP. Efficient reductive aromatization through single‐electron transfer provided the substituted nanohoops in a straightforward manner. The t Bu ester substitution pattern enables a tube‐like arrangement in the solid‐state governed by van der Waals interactions that exhibits one of the tightest packings of CPPs in tube direction, thus opening new avenues in the crystal design of CPPs. Abstract : A new synthesis provides access to different sized substituted cycloparaphenylenes (CPPs). The use of a key synthon in a sequence of macrocyclization by cross‐coupling with different reaction partners followed by aromatization allows a modular build‐up. The controlled introduction of substituents enables a tube‐like arrangement of these molecular carbon allotropes in the solid state.